International Monetary Fund Handbook : Its Functions, Policies, and Operations - Ramlogan, Parmeshwar (Manuals and Guides, 2007)
This paper describes the functions, policies, and operations of the IMF. The IMF is an independent international organization, and is a cooperative of 185 member countries, whose objective is to promote world economic stability and growth. The member countries are the shareholders of the cooperative, providing the capital of the IMF through quota subscriptions. In return, the IMF provides its members with macroeconomic policy advice, financing in times of balance-of-payments need, and technical assistance and training to improve national economic management.